Pertumbuhan Kapang Aspergillus niger dan Penicillium sp. yang Diinokulasikan pada Buah Stroberi (Fragaria sp.) (Isolation and Analysis of Proteolytic Activity of Local Actinomycetes from Aceh, Indonesia) - Lenni Fitri; Aini Syafitri; Mirryazil Jannah; Anasya Khansa Yumna; Lilis Fitria; Ira Maya Wahyuni (Universitas Syiah Kuala, 2025)
Strawberries are susceptible to attack by pathogenic fungi which can cause damage and affect the quality of strawberries. This research aims to determine the growth time of the Mould Penicillium sp. and Aspergillus niger which were inoculated on strawberries and determine the level of damage caused by the Mould Penicillium sp. and Aspergillus niger on strawberries. This research was carried out by inoculating the Mould on Penicillium sp. and Aspergillus niger on strawberries, observe the growth of these two fungi and determine the level of damage caused to strawberries due to the Mould. The results of this research show that the Penicillium sp. Mould grows faster on strawberries, starting on the third day. Meanwhile, the Aspergillus niger Mould was seen starting to grow on the fourth day of incubation. The level of damage to strawberries on day 7 was rotting and the presence of liquid produced.